Fat-Free Mass and Bone Mineral Density of Young Soccer Players: Proposal of Equations Based on Anthropometric Variables - Gomez-Campos, Rossana; Santi-Maria, Thiago; Arruda, Miguel; Maldonado, Thiago; Albernaz, Altamiro; Schiavo, Marco; Cossio-Bolaños, Marco (Frontiers in Psychology, 2019)
Background: The assessment of body composition can help optimize competitive efficiency and monitor the success of the training regimes of young soccer players. This study was to determine the predictors of Fat-Free Mass (FFM) and Bone Mineral Density (BMD) of young soccer players and to propose regression equations to estimate FFM and BDM through anthropometric variables. Methods: One hundred and sixty-seven young soccer players aged between 10.0 and 19.9 years were studied. Weight, height, trunk-cephalic length, right arm circumference, diameter of the humerus and length of the foot were assessed. FFM and BDM were determined through a dual X-ray absorptiometry (DXA). Peak Height Velocity (PHV) and chronological age were calculated. Results: Biological age (PHV), weight and circumference of the relaxed arm positively relate to FFM (R² = 41-66%). Similarly, PHV, weight, diameter of the humerus and length of the foot explain BDM in both study groups (R² = 45-82%). Six equations to predict FFM (R² = 62-69%) and six to predict BDM (R² = 69-90%) were generated. Chronological age has a limited use for predicting FFM and BDM. Conclusion: Results suggest the use and application of the regression equations as a non-invasive alternative for everyday use in soccer clubs.